The Distribution of an Invasive Species, Clidemia hirta Along Roads and Trails in Endau Rompin National Park, Malaysia. (January 2018) - Le, Cao; Fukumori, Kosuke; Hosaka, Tetsuro; Numata, Shinya; Hashim, Mazlan; Kosaki, Takashi
Invasive species pose a grave threat to many national parks. Construction of roads and trails for tourism may facilitate invasion of alien species. To understand the effect of road and trail construction on invasive species, we established six transects in three land-use types (forest interior and road or trail edges) in Endau Rompin National Park, Johor, Malaysia, where we measured the number of an invasive shrub, Clidemia hirta (Melastomataceae), canopy openness, and soil properties; compared the density of C. hirta between the three land-use types; and finally, identified soil and canopy variables affecting its abundance using generalized linear mixed models. C. hirta was found along the road and trail with density ranging from 0.0 m −2 to 33 m −2 (average: 3.8 m −2 ), but was not found in the forest interior. Generalized linear mixed models suggested that canopy openness and soil pH negatively affected the density of C. hirta along the road, as did total soil nitrogen along the trail. This suggests that C. hirta was more abundant along dark and nutrient-poor road and trail edges. The construction of narrow roads (2.0–3.8 m) and trails (0.5–2.0 m wide) at our site would be considered a relatively minor disturbance without intensive clear cuts, and C. hirta seemed to prefer habitats with such minor disturbances. In the tropical rainforests, the managers or conservationists of the national park should include consideration of the effects such as minor disturbances have on invasive species.